2022
DOI: 10.1021/acs.analchem.1c03348
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Changes in Pericardium upon Genipin Cross-Linking Investigated Using Nondestructive and Label-Free Imaging Techniques

Abstract: Tissue cross-linking represents an important and often used technique to enhance the mechanical properties of biomaterials. For the first time, we investigated biochemical and structural properties of genipin (GE) cross-linked equine pericardium (EP) using optical imaging techniques in tandem with quantitative atomic force microscopy (AFM). EP was cross-linked with GE at 37 °C, and its biochemical and biomechanical properties were observed at various time points up to 24 h. GE cross-linked EP was monitored by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
1
9
1
Order By: Relevance
“…1 B). Compared to the previous studies [ 40 , 42 ], more details are resolved here due to the higher NA of the objective lens (1.1 vs. 0.95), higher sampling rate (2048 × 2048 vs. 512 × 512), higher integration time, and averaging.
Fig.
…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…1 B). Compared to the previous studies [ 40 , 42 ], more details are resolved here due to the higher NA of the objective lens (1.1 vs. 0.95), higher sampling rate (2048 × 2048 vs. 512 × 512), higher integration time, and averaging.
Fig.
…”
Section: Resultsmentioning
confidence: 90%
“…Our previous studies showed that decellularized EP is composed of collagen and elastin fibers, of which type I collagen is predominately observed in the SHG channel and elastin in the TPEF channel [ 40 , 42 ]. Figure 1 shows TPEF and SHG overview images.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan is a biodegradable and biocompatible polymeric material from a natural source with high efficiency for preparing hydrogel carriers [25,26]. Chemically crosslinked chitosan hydrogels (CHs) can be achieved by using genipin as a natural crosslinker whichits cytotoxicity is approximately 10,000 times less than of glutaraldehyde [27,28]. According to the above mentioned facts, the main aim of the present study is the preparation and characterization of CH loaded with ZnO NPs and vancomycin for improvement of antibacterial effect and making pH-responsive hydrogel to avoid extra use of antibiotic (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a biodegradable and biocompatible polymeric material from a natural source with high efficiency for preparing hydrogel carriers (25,26). Chemically crosslinked chitosan hydrogels can be achieved by using genipin as a natural crosslinkers which its cytotoxicity is approximately 10,000 times less than of glutaraldehyde (27,28). According to the above mentioned facts, the main aim of present study is preparation and characterization of chitosan hydrogl loaded with ZnO NPs for controlling release of vancomycin and also improving its antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%